2021
DOI: 10.1016/j.jmps.2020.104281
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stress on the cross-slip energy in face-centered cubic metals: A study using dislocation dynamics simulations and line tension models

Abstract: Dislocation dynamics simulations were used to calculate the energy barrier of cross-slip via Friedel-Escaig mechanism in face centered-cubic copper. The energy barrier in the unstressed case was found to be 1.9 eV, as reported by B. Ramírez et al. [1] . The energy barrier was reduced by applying an external stress. The most effective way of reducing it, was by applying a compressive stress on the glide plane. Furthermore, it was confirmed using dislocation dynamics simulations, that both the Schmid and Escaig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The complex network of LAGBs was developed during thermal cycling, as can be seen from the histograms of the misorientation angle. It could be validated that the complex stress state was induced by thermal cycling, resulting in the formation of a dislocation network and substructures [50,51]. The misorientation of these substructures was gradually increased as the number of thermal cycles increasing until equiaxed grains were formed.…”
Section: Ebsd Analysis Of Microstructure After Thermal Cyclingmentioning
confidence: 95%
“…The complex network of LAGBs was developed during thermal cycling, as can be seen from the histograms of the misorientation angle. It could be validated that the complex stress state was induced by thermal cycling, resulting in the formation of a dislocation network and substructures [50,51]. The misorientation of these substructures was gradually increased as the number of thermal cycles increasing until equiaxed grains were formed.…”
Section: Ebsd Analysis Of Microstructure After Thermal Cyclingmentioning
confidence: 95%
“…In fact, Kang et al (2014) showed that both stress components have a comparable effect on the activation enthalpy. This assertion has been thoroughly verified using different formulations of the Line Tension (LT) model (Kang et al, 2014;Liu et al, 2019;Longsworth and Fivel, 2021), linear-elasticity models (Longsworth and Fivel, 2021;Kuykendall et al, 2020) and atomistic simulations (Kang et al, 2014;Esteban-Manzanares et al, 2020;Kuykendall et al, 2020;Liu et al, 2019). Therefore, the influence of all the stress components should be considered in the cross-slip rate.…”
Section: Introductionmentioning
confidence: 79%
“…25. The only free parameter in the theory of Malka-Markovitz and Mordehai ( 2019) is the unstressed energy barrier ∆E 0 , which can be obtained either from line tension models (Kang et al, 2014;Malka-Markovitz and Mordehai, 2019), atomistic simulations (Oren et al, 2017;Liu et al, 2019;Esteban-Manzanares et al, 2020;Kuykendall et al, 2020) or DD simulations (Ramírez et al, 2012;Longsworth and Fivel, 2021). In the present paper, the energy barrier of FCC copper ∆E 0 = 1.9 eV was obtained from DD simulations (Longsworth and Fivel, 2021) to make the work independent of other numerical results.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, alloying can reduce the material split level energy and thereby realize the simultaneous improvement of material strength and plasticity. [10][11][12] Various studies have [13][14][15][16][17][18] used molecular dynamics theory to simulate the evolution of FCC unit cell dislocations. He et al 19 proposed a single-bit error-based model to quantitatively predict the stress-strain behavior of micron-scale FCC and bodycentered cubic metal cells.…”
Section: Introductionmentioning
confidence: 99%